Liberalism and Authorial Influence in Henrik Ibsen’s Hedda Gabler - Nurfaizi, Fiqhi Haditya (Journal of Literature, Linguistics, & Cultural Studies, 2024)
Liberalism is an ideology that emphasizes the importance of individual freedom. This understanding that emerged in the 18th century influenced the development of society through social aspects, and one form of influence of liberalism is when social aspects can influence a writer to consciously express the values ​​of liberalism which focus on individual freedom in the characters. characters in a literary work. This research will explain the values ​​of liberalism and what social factors influence the author's ideology through the author's sociological approach. The object of this research is a drama script entitled Hedda Gabler (1890) by Henrik Ibsen which shows the values ​​of liberalism through several of its characters. The aim is to find out what aspects of liberalism are depicted by several characters in the drama Hedda Gabler and what social factors influence the author's ideology. Researchers use the sociological theory of authors Warren & Wellek, and the liberalism of John Locke. Then, using the literary criticism method, the researcher found several findings, namely 1.) Liberalism aspects in drama texts Hedda Gabler shown through dialogue between characters; 2.) The author's life background which influences the author's ideology is shown through the author's biography and dialogue excerpts in the drama script Hedda Gabler. Additionally, aspects of liberalism are depicted by several characters Hedda Gabler are natural rights and property rights. Based on the research results, this research can be used as a model for future researchers in finding detailed data about a writer through literary works.